Health Belief Model Analysis on the Relationship Between Ergonomic Behavioral Awareness and Low Back Pain in Pregnant Women: A Cross-Sectional Mediation Study - Zuhri, Saifudin; Suwarni, Sri (Journal of Applied Nursing and Health, 2025)
Background: Low back pain is a common health complaint experienced by pregnant women, both nationally and regionally. Its high prevalence highlights the need for attention to preventive strategies during pregnancy. This study aims to analyze the role of the Health Belief Model (HBM) in mediating the relationship between ergonomic behavioral awareness and the incidence of low back pain in pregnant women. Methods: A quantitative, cross-sectional survey was conducted among 140 pregnant women in their second or third trimester who reported low back pain. Data were collected using structured questionnaires and analyzed using Structural Equation Modeling (SEM) based on Smart PLS. This study was reported following the STROBE guidelines for cross-sectional studies. Results: Ergonomic behavioral awareness had a strong negative effect on the incidence of low back pain (β = -0.715; p < 0.001), and a positive impact on the Health Belief Model (β = 0.801; p < 0.001). The Health Belief Model also had a statistically supported negative effect on low back pain (β = -0.264; p < 0.001). Furthermore, a significant indirect effect was observed between ergonomic awareness and back pain through the Health Belief Model as a mediating variable (β = -0.211; p < 0.001). Conclusion: Ergonomic awareness plays a crucial role in reducing low back pain in pregnant women, both directly and indirectly through improved health beliefs. Strengthening HBM components may enhance ergonomic practices, which could be integrated into routine pregnancy education and health promotion efforts.